Responses of nuclear receptor HR96 to the toxic dinoflagellate Prorocentrum lima in Crassostrea ariakensis - Kuan-Kuan Yuan; Ya-Xin Liu; Xiu-Lin Yang; Yu-Jie Liu; Hong-Ye Li; Wei-Dong Yang (Ecotoxicology and Environmental Safety)
Diarrhetic shellfish toxins (DSTs) are widely distributed and the most common algal toxins and their metabolic detoxification mechanism in shellfish remains poorly understood. Nuclear receptors are pivotal in regulating the detoxification of xenobiotics across various species. In this study, we identified the homologous sequence HR96 of the PXR/VDR/CAR nuclear receptor gene in Crassostrea ariakensis, and found that it may play an important role in resistance to DSTs. Molecular docking results showed that DSTs could be used as ligands to activate the nuclear receptor HR96. After exposure to Prorocentrum lima (a DST-producing dinoflagellate), the DSTs content in the digestive gland tissue of C. ariakensis increased during the accumulation stage, followed by a decrease and then an increase with time during the depuration stage. With few exceptions, the expression levels and protein content of HR96 and related detoxification genes increased throughout the toxin accumulation and depuration stage, suggesting that HR96 may mediate the regulation of genes involved in metabolic detoxification, thereby protecting oysters from the toxic effects of DSTs. During the depuration stage, the toxin content in digestive gland tissues fluctuated but remained at a high level, and the tissue damage was not significantly reduced, which may be related to the migration of toxins among different tissues. Our findings may provide a new perspective on the response of oysters to DSTs and contribute to a deeper understanding of the role of nuclear receptors in environmental adaptation of bivalves.